MAPPING OF APHID SPECIES ASSOCIATED WITH POTATO IN INDIA USING MORPHOLOGICAL AND MOLECULAR TAXONOMIC APPROACHES - Bhatanagar, Anuj (Potato Journal, 2018)
Potato J (2017) 44 (2): 117-125Anuj Bhatnagar1 , Shridhar Jandrajupalli2 , Vallepu Venkateswarlu2 , Kamlesh Malik1 , Mohd Abas Shah3 and BP Singh2ABSTRACT: Field surveys were carried out from 2011 to 2015 in different potato growing areas of India for collecting aphid species infesting potato and the aphid species were identified using molecular and morphological approaches. Thirteen species of aphids were identified from different regions of the country. Myzus persicae (Sulzer) and Aphis gossypii Glover were the most common species and high population of these aphids was recorded on potato during first week of February in different parts of Uttar Pradesh. Aulacorthum solani (Kaltenbach) and Brachycaudus helichrysi (Kaltenbach) are being reported for the first time from India from Faizabad region of Uttar Pradesh. The black bean aphid, Aphis fabae Scopoli was identified from Manikpur and Tanda while as green citrus aphid, Aphis spiraecola Patch, oleander aphid, Aphis nerii Rothschild and coriander aphid, Hydaphis coriandri (Das) apart from Myzus persicae and Aphis gossypii were identified from Meerut during October to December. Rice root aphid, Rhophalosiphum rufiabdominalis (Sasaki), Myzus persicae, Aphis gossypii and Aphis spiraecola were identified from Jalandhar (Punjab). These findings need to be taken into consideration in the pest management for healthy seed potato production.